How do you solve the following system?: -x -2y =1, 9x -y = -1

1 Answer
Nov 14, 2015

We can solve this question by finding the value of x with respect to y from both equations. Since the value of x should be equal, the equations thus obtained can be solved for y. And then either of the initial equations can be used to find x.

Explanation:

  1. -x-2y = 1 => -x=1+2y => x=-(1+2y) ----EQUATION 1
  2. 9x-y=-1 => 9x=y-1 => x=1/9*(y-1) ----EQUATION 2

Equating the values of x from EQUATION 1 and EQUATION 2;
we have;
-(1+2y)=1/9*(y-1)
=> -9-18y=y-1
=>-18y-y=-1+9
=>-19y=8
=>y=-8/19

Using EQUATION 1;
x=-(1+2y)
=>x=-(1+2*(-8/19))
=>x=-(1-16/19)
=>x=-3/19

So there you have it!!

x=-3/19
and
y=-8/19